Sequence variants in ARHGAP15, COLQ and FAM155A associate with diverticular disease and diverticulitis - Snaevar Sigurdsson (Nature Portfolio, 2017)
A hallmark of diverticular disease is pouches in the bowel wall which can become infected and inflamed, causing the more severe diverticulitis. Here, the authors report the first genome-wide association study on these interconnected conditions and identifyARHGAP15, COLQ and FAM155Aas novel risk loci.